Exploring the Nonlinear Effect of Intellectual Capital on Financial Performance: Evidence from Listed Shipping Companies in China - Jian Xu; Yi Zhang (Complexity)
Intellectual capital (IC) is reckoned as a significant driving force of competitive advantage and financial sustainability of any organization. The study’s objective is to explore the nonlinear effect of IC and its components on financial performance (FP) of China’s listed shipping companies over a six-year period (2014–2019). The modified Value Added Intellectual Coefficient (MVAIC) model is used to systematically assess IC. The empirical results show an inverted U-shaped relationship between the aggregate IC and FP (measured through return on assets). Regarding IC components, human, relational, and innovation capitals have an inverted U-shaped relationship with FP, while the quadratic relationship between structural capital and FP is not significant. In addition, physical capital has a U-shaped relationship with FP. This study will offer some new insights for corporate managers to improve firms’ FP by effectively utilizing their IC resources.